2020
DOI: 10.1029/2019tc005834
|View full text |Cite
|
Sign up to set email alerts
|

Active Fault Scarps in Southern Malawi and Their Implications for the Distribution of Strain in Incipient Continental Rifts

Abstract: The distribution of deformation during the early stages of continental rifting is an important constraint on our understanding of continental breakup. Incipient rifting in East Africa has been considered to be dominated by slip along rift border faults, with a subsequent transition to focused extension on axial segments in thinned crust and/or with active magmatism. Here, we study high-resolution satellite data of the Zomba Graben in southern Malawi, an amagmatic rift whose topography is dominated by the west-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 108 publications
(225 reference statements)
2
51
0
Order By: Relevance
“…The observation that intrarift faulting may contribute to cumulative rift opening in at least some parts of the North Basin is consistent with the formation of these faults early in the rift history (McCartney & Scholz, ; Mortimer et al, ) and their continued activity over the life of the rift (McCartney & Scholz, ). The proportion of deformation accommodated by intrarift faults in the North Basin of the Malawi Rift (~20–25%) is greater than in the Tanganyika Rift, where the intrarift faults account for ~10% of total extension (Muirhead et al, ) but less than in the southern Malawi Rift, where intrarift faults accommodate ~55% of Quaternary extension (Wedmore et al, ). One possible explanation for this regional pattern is progressive localization on the border fault (Cowie et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The observation that intrarift faulting may contribute to cumulative rift opening in at least some parts of the North Basin is consistent with the formation of these faults early in the rift history (McCartney & Scholz, ; Mortimer et al, ) and their continued activity over the life of the rift (McCartney & Scholz, ). The proportion of deformation accommodated by intrarift faults in the North Basin of the Malawi Rift (~20–25%) is greater than in the Tanganyika Rift, where the intrarift faults account for ~10% of total extension (Muirhead et al, ) but less than in the southern Malawi Rift, where intrarift faults accommodate ~55% of Quaternary extension (Wedmore et al, ). One possible explanation for this regional pattern is progressive localization on the border fault (Cowie et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It would also be somewhat surprising because the dimensions of the Livingstone Border Fault are already larger than what is estimated to be mechanically favorable (Accardo et al, ; Olive et al, ; Scholz & Contreras, ), which would predict less activity on the border fault and more activity on intrarift faults in the future. Another possible explanation is that the observed variations could reflect differences in crustal rheology between different parts of the Western Rift, resulting in different styles of faulting (Wedmore et al, ; Williams et al, ). For any of the scenarios, our results suggest that intrarift faults have contributed to rift opening in the northern Malawi Rift.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We used scarp height as a proxy for displacement (e.g. Morewood and Roberts, 2000;Hodge et al, 2018bHodge et al, , 2019Wedmore et al, 2020) and identified segments based on local minima in the along-strike scarp height profile. We used adapted versions of the SPARTA scarp measuring tools (Hodge et al, 2019) to measure the height of the fault scarp along the Thyolo fault on the 12 m DEM.…”
Section: Fault Segmentation Analysismentioning
confidence: 99%